Study of the Penetration and Diffusion Characteristics of Inorganic Solidified Foam in Rock Fractures - Yi Lu; Tao Wang; Qing Ye (Advances in Materials Science and Engineering)
To explore the penetration and diffusion law in coal and rock fractures when inorganic solidified foam (ISF) is used to prevent coal fire, the penetration experiment was conducted; the results showed that the penetration pressure fluctuates within a certain range and decreases with the diffusion distance. In the XY plane, the diffusion pattern presents an ellipsoid shape, and the diffusion area becomes increasingly large over time; in the XZ plane, the foam fluid penetration changes from dense to loose in the X direction and it does not undergo downward penetration and diffuses via its own weight in the Z direction; in the YZ plane, it is loose on the left and dense on the right. The viscosity of ISF was tested and then the time-varying formula was fitted. The formula of the effective diffusion radius for foam fluid diffusing in the fracture channel was determined theoretically. The permeability coefficient and other related parameters were calculated in terms of the penetration pressure and diffusion time of two monitoring points. At last, the prediction formula of effective diffusion distance of foam fluid was verified with the remaining seven monitoring points and all the relative error of monitoring is within 10%.